Urinary Tract Infections Detection with Molecular Biomarkers - Jiayi Sun; Kai Cheng; Yanyun Xie (Biomolecules, 2024)
Urinary tract infection (UTI) is the most prevalent kind of pathogenic bacteria infection, and the midstream urine culture is regarded as the gold standard in UTI diagnosis. Recently, even with modern media and techniques such as polymerase chain reaction (PCR), urinary cultures still create a considerable workload for hospital laboratories. Other UTI-detecting methods, such as flow cytometry and lateral flow immunoassay, suffer from various drawbacks like long time consumption and low sensitivity. Therefore, looking for reliable biomarkers in UTI is urgently needed. In this review, the current definitions of UTI can be basically divided into two main categories: uncomplicated UTI and complicated UTI. In light of anatomical sites, it can be classified as either lower UTI or upper UTI. We take the classification of UTI as a clue and review the reported extensive literature to classify the existing studied markers into the following three categories: Biomarkers used clinically; Promising biomarkers; and Controversial biomarkers. Particularly, the nucleic acid-associated, metabolomic, and lipidomic biomarkers are highlighted. At the end, we discuss the challenges and prospects of biomarkers in UTI, hoping to further inspire the diagnosis of UTI.